HUBUNGAN KEMAMPUAN SOSIAL DAN KECERDASAN EMOSIONAL TERHADAP FUNGSI EKSEKUTIF ANAK USIA DINI - Wulandari, Asnawati; Susanti, Debie (Journal of Early Childhood Education (JECE), 2023)
Early childhood education is the spearhead of the success of early childhood development, therefore research is conducted to see and analyze the relationship between social skills and emotional intelligence on the executive function of early childhood in order to provide appropriate follow-up stimulation in the future. The method used in this study is a quantitative approach. The research sample was 99 children of kindergarten group A students in Bekasi City, West Java Province, who were selected through multistage cluster random sampling technique where the sample selection was done in two or more stages. Data collection techniques were carried out through questionnaires administered online using Google Form filled by Teachers and Parents. Data analysis techniques used include analysis test and hypothesis test. The results showed that there was a positive relationship between (1) social skills and executive function of children, (2) emotional intelligence and executive function of children, (3) social skills and emotional intelligence and executive function of children. This means that the results of this study can be concluded that there is a relationship between social skills and emotional intelligence on the executive function of early childhood.